PENURUNAN NYERI MYOFASCIAL TRIGGER POINT SYNDROM (MTPS) OTOT BISEP DAN TRISEP DENGAN METODE GELATIK - Lestari, Widia (JURNAL MEDIA KESEHATAN, 2017)
The incidence of MTPS is still high, especially on the field workers in theMunicipal Water Company (PDAM) of Bengkulu City with signs and symptoms of painin the biceps and triceps. Isometric exercise is one of the practical and economical waysto reduce pain. The aim of the research was to know the effect of isometric exercisemovement on the decrease of biceps and tricep's biceps BMPS on the field worker inPDAM Kota Bengkulu. This research was an analytic research, which uses one grouppre-test post-test design. The sample in this research was PDAM Bengkulu field workeris 21 people. Data collection by measuring the scale of pain in the biceps and triceps.Data analysis was conducted in quantitative manner ie univariate and bivariate. Based onthe result of the research, it was found that the average value of pain scale beforeperforming gelatik is 3.52 with 95% CI 3,13-3,92. After 2 weeks of gelatik was done asmuch as 6 times got the pain scale of respondent was 3,00 with 95% CI 2,71-3,29Wilcoxon test result got p value <0,05 (0,012). This method is expected to be applied tothe program of PDAM Kota Bengkulu with the implementation of gelatik 3 times a weekto reduce the pain of MTPS.